Theranos, Inc. : managing risk in a high-flying biotech start-up - Kelley, Caitlin; Lee, Shareen; Shields, Virginia; O'Rourke, James S., 1946- (London : The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame, 2017)
The case describes how a start-up bio-tech company covered up failed quality control standards leading to an expose in the Wall Street Journal. The study examines the effects of this scandal both on the value of Theranos and its ability to continue manufacturing medical supplies.
Originally published in Kelley, C., Lee, S., Shields, V. & O'Rourke, J. (2017). Theranos, Inc.: Managing risk in a high-flying biotech start-up. Notre, Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Theranos, Inc; Wall Street journal; Biotechnology industries -- Public opinion